2009
DOI: 10.4049/jimmunol.0901026
|View full text |Cite
|
Sign up to set email alerts
|

The α-Isoform of p38 MAPK Specifically Regulates Arthritic Bone Loss

Abstract: Pharmacological inhibitors have provided evidence for the key role of p38 MAPK in osteoclast differentiation and in inflammation-induced bone loss. However, these inhibitors block more than one of the four p38 isoforms, usually p38α and p38β, and sometimes also other kinases such as JNK3. We show in this study that p38α is the main p38 isoenzyme expressed in the osteoclast precursors and in the mature osteoclasts. p38α as well as its downstream substrates were phosphorylated in osteoclast progenitors stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 57 publications
2
64
1
1
Order By: Relevance
“…Histomorphometric analysis was performed on methacrylate-embedded undecalcified plastic sections stained with von Kossa's stain and with Goldner's stain for bone. Histologic and immunohistologic analyses were performed as described previously (30,31). All quantifications were performed by digital image analysis (OsteoMeasure; OsteoMetrics).…”
Section: Methodsmentioning
confidence: 99%
“…Histomorphometric analysis was performed on methacrylate-embedded undecalcified plastic sections stained with von Kossa's stain and with Goldner's stain for bone. Histologic and immunohistologic analyses were performed as described previously (30,31). All quantifications were performed by digital image analysis (OsteoMeasure; OsteoMetrics).…”
Section: Methodsmentioning
confidence: 99%
“…Osteoclast precursors and mature osteoclasts highly express p38a but no other p38 members. 45 Once again, first evidence highlighting the role of p38a in osteoclastogenesis has come from in vitro experiments employing the RAW264 cell line and primary bone marrow cells with selective p38 inhibitors and dominant negative forms of p38 signaling components. [46][47][48] In those cells, p38a functions downstream of RANK after stimulation by RANKL (the proresorptive cytokine that is necessary and sufficient for osteoclastogenesis) to stimulate osteoclast formation, maturation and bone resorption 46,47 (Figure 3).…”
Section: The P38 Mapk Signaling Pathway In Osteoclastsmentioning
confidence: 99%
“…47 Consistent with those data, mice with post-developmental deletion of the p38a-encoding gene under the control of the inducible Mx1 promoter display reduced osteoclast number, low bone resorption and increased bone mass under physiological conditions, and are protected against TNF-a-induced arthritis and systemic bone loss. 45 Although the Mx1-cre deleter strain is known to induce complete gene excisions in hepatocytes and hematopoietic cells, and variable deletions in other cell types, 49 this decreased osteoclastogenesis has been shown to be cell autonomous, as bone marrow hematopoietic cells lacking p38a cannot differentiate into mature osteoclasts in response to macrophage colonystimulating factor (M-CSF) and RANKL treatment in vitro. 45 MKK3 and MKK6 have been found to be required for osteoclastogenesis in vitro.…”
Section: The P38 Mapk Signaling Pathway In Osteoclastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately it has been demonstrated that p38 MAPK signaling is essential for skeletogenesis and bone homeostasis in mice (Greenblatt et al, 2010;Thouverey and Caverzasio, 2012). However, it has been shown that an over increase of p38 MAPK phosphorylation contributed to potentiation of osteoclastogenesis, and arthritic bone loss (Karsdal et al, 2003;Böhm et al, 2013). The activation of MAPK proteins, through the combined activities of the matrix-degrading MMPs, such as MMP2, MMP7 and MMP9, has been observed in osteoarthritic-cartilage-damage human models (Malemud, 2006;Ding et al, 2010).…”
Section: Introductionmentioning
confidence: 99%